Comparing Two Types of Diagnostic Items to Evaluate Understanding of Heat and Temperature Concepts - Chu, Hye-Eun; Chandrasegaran, A.L.; Treagust, David (2018)
The purpose of this research was to investigate an efficient method to assess year 8 (age 13-14) students' conceptual understanding of heat and temperature concepts. Two different types of instruments were used in this study: Type 1, consisting of multiple-choice items with open-ended justifications; and Type 2, consisting of two-tier multiple-choice items. Each of the instruments was administered to two separate cohorts of 173 and 143 year 8 students of similar achievement. The findings indicated that the students were better able to show their understanding in the two-tier multiple-choice items. Hence, based on this investigation, two-tier multiple-choice items may be more suitable for evaluating year 8 students' understanding of science concepts.